Relationship between Job Satisfaction and Organizational Citizenship Behaviour (OCB): The Moderating Role of Team Commitment - Siti Noor Asekin, Jaafar (2010)
The purpose of this study was to examine the relationship between job satisfaction and organizational citizenship behaviour (OCB), and to determine whether team commitment moderates the relationship between job satisfaction and OCB. Data were taken from 94 Army personnel that working in military base located in Mahkota Camp, Kluang, Johor. This study used the simple random sampling technique. The questionnaire was divided into four section, namely Section A (demographic factors - consist 7 items), Section B (job satisfaction - 72 items), Section C (organizational citizenship behaviour - 21 items), and Section D (team commitment - 12 items). This study was used frequency analysis, descriptive analysis, Pearson correlation, and One-way ANOVA to test the hypotheses. The results suggested that job satisfaction was significant related to organizational citizenship behaviour. The study also indicates that team commitment does moderates the relationship between job satisfaction and OCB. Demographic factors, age was found to be related to OCB practices, while tenure was found not related to OCB practices.